Determinants of green energy investment—financial drivers and equitable transition - Wei Lou; Shibao Lu; Meng Li; Farhad Taghizadeh-Hesary (Humanities & Social Sciences Communications)
Abstract This study examines the factors influencing green energy investment in China from 2015 to 2022 using macroeconomic and financial data. Fully Modified Ordinary Least Squares (FMOLS) regression analysis identifies a strong positive relationship between green bond issuance—used as a proxy for green finance—and renewable energy investment, underscoring its critical role in the energy transition. However, private investment in public equity (PIPE) negatively correlates with renewable investment, suggesting a misalignment with equitable climate goals. Economic distress, measured by the misery index, is associated with increased renewable investment, likely reflecting a preference for stable, socially responsible assets during downturns. In contrast, rising income levels correspond to a decline in green investment, indicating that wealthier individuals may prioritize energy-intensive consumption. Policy recommendations to promote equitable green finance include aligning green bond standards, expanding RMB-denominated issuance domestically and internationally, and enhancing transparency to attract responsible investors. Strengthening these measures can help ensure the equitable distribution of benefits from renewable energy investments, supporting China’s transition to a sustainable and just energy system.